Penggunaan Arabic Cover Song Dalam Pembelajaran Shorof di Pondok Pesantren: The Use of Arabic Cover Songs in Shorof Learning at Islamic Boarding Schools - Mohammad Sofi Anwar; Putri Kholida Faiqoh (Jurnal Pendidikan Bahasa Arab dan Budaya Islam, 2024)
The evaluation of Shorof learning in Islamic boarding schools has so far been limited to tashrif activities, determining changes in words from one form to another. While such evaluation activities are not incorrect, as developing tashrif skills is indeed one of the learning objectives, they can be perceived as monotonous and less engaging. This research is a qualitative descriptive study of the literature aimed at theoretically examining the use of Arabic Cover Songs in the evaluation of Shorof learning activities in Islamic boarding schools. Data for this study are derived from books, journals, previous research, and other references related to the theoretical study of Shorof learning with songs (Arabic Cover Songs) in Islamic boarding schools. The data collection method used is documentary study, analyzed using the Miles and Huberman model. The analysis involves three stages: data collection, data presentation, and conclusion drawing. The research results revolve around the evaluation of Shorof learning with Arabic Cover Songs, providing examples of Shorof learning evaluation activities based on Arabic Cover Songs in Islamic boarding schools including guessing song lyrics, memorizing song lyrics, song lyrics crossword puzzles, song lyrics rain, guessing lyrics puzzles, and throwing fi'il.